Dynamics of land use/cover changes and plant diversity in Tubah Sub-Division, Cameroon - Awo Miranda Egbe; Fonge Beatrice Ambo; Angwi Judith T; Tabot Pascal Tabi (Sustinere: Journal of Environment and Sustainability, 2022)
Land use change detection is often conducted to critically discern trends, causes, and their impacts on the landscape to enhance decision-making for conservation of biodiversity and ecological functions. The objectives of the study were to evaluate Land Use and Land cover changes in Tubah Sub-Division, Cameroon, from 1986 to 2017, and to determine plant diversity and abundance in areas with different land uses. Field surveys were carried out to determine the diversity of this area, eight 50x50m sample plots were established in four different sites and trees and shrubs with diameter at breast height (DBH≥10mm) were sampled. Primary data was obtained through field observations and ground truthing in order to confirm observations on satellite images. Land use maps were produced using GIS ArcGis 10.2. Images were extracted for the years 1986, 1996, 2006, and 2017. A total of 173 species were recorded in all the sites belonging to 63 families and 146 genera. The fallow land and secondary forest were the most diverse of all the sites with the highest Shannon index of H′= 3.09 and H′= 2.97 respectively. The least diverse were the agricultural and grazing lands, with H′= 1.39. Analysis of the GIS data revealed a decline in vegetation cover of 90.24 hectares from 1986-1996, 23.76 ha from 1996-,2006 and 86.70 ha from 2006-2017. Settlement areas increased by 63.64 ha from 1986-1996, 53.37 ha from 1996-2006 and 15.36 ha from 2006-2017. Water bodies reduced from 1986-1996 by 7.34 ha, 14.28 ha from 1996-2006 and 3.56 ha from 2006-2017. Bare ground increased by 135.88 ha from 1986-2017. Field observations revealed that agricultural intensification, construction of buildings, unsustainable logging and grazing were the major causes affecting plant diversity in Tubah Sub-Division. The study’s outcomes are critical for future land-use planning exercises and the long-term conservation of the biodiversity and water sources for the communities. The population of Tubah should be educated on sustainable land use management and biodiversity conservation.